2018
DOI: 10.1002/elan.201800651
|View full text |Cite
|
Sign up to set email alerts
|

A 3,5‐DistyrylBODIPY Dye Functionalized with Boronic Acid Groups for Direct Electrochemical Glucose Sensing

Abstract: The synthesis and characterization of a novel BODIPY dye functionalized with bis‐boronic acid groups to enable direct glucose sensing through selective recognition of carbohydrates is reported. Styrylation with boronic acid groups at the 3,5‐positions of the BODIPY core results in an extension of the π‐conjugation system of the dye and in a red‐shift of the main absorption band from 500 to 637 nm. The functionalized BODIPY dye was adsorbed on a glassy carbon electrode using the drop and dry method. Modified an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…Links between 11 B chemical shifts and diol binding sites had been identified previously 36 and our work provided further evidence of a relationship. The conjugates with a 1,3-diol binding site showed O-B-O angles that were also greater than the ideal tetrahedral angle (but smaller than the angle in 3Ra/4Ra) and demonstrated 11 B chemical shifts in the range of 0-2 ppm. The conjugates with 1,2-diol binding sites showed O-B-O angles slightly smaller than that of the tetrahedral ideal ranging from ∼104-108°.…”
Section: O-bodipy Binding Preferencessupporting
confidence: 83%
See 2 more Smart Citations
“…Links between 11 B chemical shifts and diol binding sites had been identified previously 36 and our work provided further evidence of a relationship. The conjugates with a 1,3-diol binding site showed O-B-O angles that were also greater than the ideal tetrahedral angle (but smaller than the angle in 3Ra/4Ra) and demonstrated 11 B chemical shifts in the range of 0-2 ppm. The conjugates with 1,2-diol binding sites showed O-B-O angles slightly smaller than that of the tetrahedral ideal ranging from ∼104-108°.…”
Section: O-bodipy Binding Preferencessupporting
confidence: 83%
“…This correlation would seem to suggest that the greater the O-B-O angle, the lower the 11 B chemical shift (upfield shifted), with the exception being the angle created by the 1,4-diols. Looking closer at the 1,2-diol region, it was observed that pyranoses typically had 11 B chemical shifts in the range of 4.5-5.5 ppm and furanoses had 11 B chemical shifts in the range of 5.5-6.1 ppm. Exceptions were found for the exocyclic O5-O6 bound BODIPY in 3Ga and 4Ga and the trans-diol BODIPY of the septanose 4Gc.…”
Section: O-bodipy Binding Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of them is boronic acid directly substituted to a fluorophore, such as pyrene (Yu and Yam, 2009), antrecene (Sugita et al, 2019), Bodipy or chiral binaphthols (Liang et al, 2008). In this respect, boronic acid functional group as a saccharide receptor moiety has been directly attached to a Bodipy scaffold to sense the glucose in solution (Zhai et al, 2012;Ndebele et al, 2019). The disadvantage of these systems is that the photostability and UV excitation of the dye could change due to the boronic acid functionality (Camara et al, 2002).…”
Section: Introductionmentioning
confidence: 99%